Match each function with the corresponding function formula when h(x) = 5 - 3x and g(x) = -3 x + 5.


1.

k(x) = (3h - 5g)(x)

2.

k(x) = (h - g)(x)

3.

k(x) = (5g + 3h)(x)

4.

k(x) = (3g + 5h)(x)

5.

k(x) = (g + h)(x)

6.

k(x) = (5h - 3g)(x)

Respuesta :

Answer:

To match each functions with the corresponding function formula when h(x) = 5 - 3x and g(x) = -3 x + 5.

1. k(x) = (3h - 5g)(x)

  = = 3(5 - 3x)-5(-3 x + 5)

 = = 15 - 9x + 15x - 25

  K(x) = -10 + 6x

2.  k(x) = (h - g)(x)

    = = (5 - 3x) - (-3 x + 5)

 = = 0

k(x) = 0

3. k(x) = (5g + 3h)(x)

 = = 5(-3 x + 5)+3(5 - 3x)

 = = -15x + 25 + 15 - 9x

 k(x) = - 24x +40

4. k(x) = (3g + 5h)(x)

  =  = 3 (-3 x + 5) + 5(5 - 3x)

 = = -9x + 15 +25 -15x

 k(x) = -24x + 40

5.  k(x) = (g + h)(x)

   = = (-3 x + 5) + (5 - 3x)

k(x)  = -6x + 10

6.  k(x) = (5h - 3g)(x)

 = = 5(5 - 3x) - 3(-3 x + 5)

= =25 - 15x + 9x - 15

k(x) = 10 - 6x

Answer: 1. k(x) = (5g + 3h)(x) ---------------- 5. k(x)=40-5(3^x)-9x

2. k(x) = (3h - 5g)(x) ---------------- 6. k(x)=5(3^x)-9x-10

3. k(x) = (3g + 5h)(x) ---------------- 1. k(x)=40-3^x+1-15x

4. k(x) = (5h - 3g)(x) ----------------- 3. k(x)=10+3^x+1-15x

5. k(x) = (h - g)(x) ----------------- 2. k(x)=3^x-3x

6. k(x) = (g + h)(x) ----------------- 4. k(x)=10-3^x-3x

ACCESS MORE